The Role of Electronic Evidence in the Civil Case Evidence Process - Nikhil Joshi; Rohan Kumar; Priya Patel (Rechtsnormen: Journal of Law, 2025)
Background. The increasing reliance on digital technology has significantly impacted legal proceedings, especially in civil cases, where electronic evidence plays an increasingly central role. With the proliferation of digital communications, social media, and electronic transactions, the types of evidence available have expanded, leading to new challenges for legal professionals in managing and evaluating such evidence. Electronic evidence is now considered a crucial aspect of civil litigation, yet questions remain regarding its admissibility, reliability, and role in the broader evidence process. Objective. This study aims to explore the role of electronic evidence in the civil case evidence process, focusing on its impact on case outcomes, the challenges associated with its handling, and its integration into traditional legal frameworks. Method. A qualitative research design was employed, utilizing case studies, legal documents, and expert interviews. The data was analyzed to examine the practical applications of electronic evidence in civil cases and the associated legal and procedural challenges. Results. The findings reveal that while electronic evidence is essential in modern civil litigation, it often faces challenges in terms of authentication, privacy concerns, and its acceptance in court. The study also found that the increasing complexity of digital evidence requires enhanced legal procedures for handling and presenting such evidence effectively. Conclusion. Electronic evidence plays a pivotal role in civil litigation, but its integration into the evidence process requires further legal refinement to address emerging challenges effectively.